PENGARUH NATTOKINASE TERHADAP DAYA KERJA Metformin HCl DALAM MENURUNKAN KADAR GLUKOSA DARAH PADA TIKUS PUTIH JANTAN (Rattus norvegicus) GALUR WISTAR - Okta, M Sandila; Sofia, Vivi (Universitas Ahmad Dahlan, 2013)
Interaction of modern drug and traditional drug is an issue that needs to beexamined, not least in the treatment of diabetes mellitus. Nattokinase is a nutraceuticalproduct that can be used in conjunction with antidiabetic oral drugs that allows theinteraction. This study aims to determine the effect of Nattokinase against their powerMetformin HCl in decreasing of blood glucose levels male white rats (Rattusnorvegicus) Wistar. This study uses an oral glucose tolerance test with glucose loadingdose of 4.5 g/kg. Animals test used were white male Wistar rats aged 2-3 monthsweighing 150-200 g, 20 rats were divided into 4 groups, each group consisted of 5 rats.Group I as a negative control group was given tween 80 - span 80, group II as a positivecontrol group was given metformin HCl doses of 45 mg/kg, group III was givenNattokinase dose 300 mg/kgBB, group IV given nattokinase 300 mg/kgBB 1 hour thenwere given metformin HCl. 30 minutes later all treatment of groups were given glucose.When treatment is considered as a time at-0. The given of glucose is considered as thetime at-30. Blood sampling via the tail at 0, 30, 60, 120, and 180. Blood glucose levelswas measured with the Easy Touch. The effect of decreasing blood glucose levelsindicated by the value of LDDK0-180 (Regional Area Under the Curve minute 0 tominute 180 of the graph time vs blood glucose levels). The data can be testedstatistically by Kruskal-Wallis and Mann Whitney with a level of 95%. The resultsshowed that administration of Metformin HCl after 1 hour administration Nattokinasecan be decreased 52.22% of Metformin HCl.